Parámetros de elaboración de fariña fortificada a partir de Manihot esculenta Crantz, (yuca) variedad piririca - Ramirez Perez, Bruno Francisco (2022)
The present research was developed in part in the facilities of the Pilot Plant of preserves of the Faculty of Food Industries and the other part in the facilities of Empresa Natural Chacruna E.I.R.L. Being the raw material the cassava Manihot esculenta Crantz, pyric variety, which was acquired in the Caserío Ángel Cárdenas. First area, Carretera Iquitos-Nauta Km: 35.5, being its location Geodesic: 18M 0695814-Altitude 132 masl. Once the cassava arrived at the Plant, we proceeded to perform the analysis of the raw material following the methods of the A.O.A.C, of the year 2018, then it was processed following the steps: heavy, classified / selection, peeled, washed, fermented (48 hours immersed in drinking water, and then perform chemical physical analysis), crushed, rest (moment where it is fortified), then sifted (separation of the starch), the by-product of cassava rich in fibers, was subjected to a roasting in the facilities of the natural company Chacruna E.I.R.L, using a toaster, all of stainless steel which uses 4 gas balloons, to toast the product and obtain almi-free pharyndón, the two drying treatments that were 110 and 140 oC, for which in the first treatment, the roasting time was 6 hours and the second treatment was 4 hours, once the fariña yield was 13 percent, obtained, it was subjected to the chemical, microbiological physical analyses (determination of molds using the method of the I.C.M.S.F.), and acceptability analysis (20 untrained panelists were used, using a hedonic scale, evaluating: texture, color, smell, taste and general appearance), then with these results the statistical tests of acceptability of the two products (two treatments) were performed, using the statistical software SSPS, version 25, applying nonparametric tests , where they corroborate that the treatment (T2), is the one that obtained the best rating, being and concluding that it is the ideal treatment.